The Effects of On-the-job and Workshop Training Methods on Performance of Midwives in Report Writing - Motahareh Loeloe; Sedigheh Yousefzadeh; Habibollah Esmaily; Seyed Ariya Hejazi (Mashhad University of Medical Sciences, 2020)
Background & aim: One of the most important professional duties of midwives is writing the reports, which considered as legal documents. Incomplete reports can resulted in misunderstanding and even lead to filing charges against midwives by the legal authorities. Therefore, this study aimed to investigate the effects of on-the-job training (OJT) and workshop training methods on the report-writing performance of the midwives working in the teaching hospitals. Methods: This quasi-experimental study was conducted on 70 midwives working in Imam Reza and Ghaem hospitals, Mashhad, Iran, in 2018, who randomly allocated to two OJT (N=35) and workshop group(N=35).  Following obtaining an informed consent, a pre-test examination was performed before the intervention. The OJT group received the required trainings before and at the patients' bedside during their work shifts. Workshop training group received lectures and practical works as the comparison group. The performance scores of the midwives were compared in both groups in three stages of pre-intervention, during the intervention, and one month post-intervention. All the data were analyzed by Mann-Whitney U test and Friedman test using SPSS software (version 24). Results: Our findings showed no significant different in terms of pre-intervention performance score (P=0.539). However, the scores of performance in the OJT group were significantly higher than those in the workshop group during the training program and one month post-intervention (P ˂ 0.05). Conclusion: We argue that the OJT method can be considered an effective intervention in improving the report-writing performance of midwives.